Myocardial injury in patients hospitalized for SARS-CoV19: a maker or a marker of prognosis?. (14th October 2021) - Montalto, C; Ghio, S; Pagnesi, M; Cappelletti, A; Baldetti, L; Baldi, E; Lombardi, C; Lupi, L; Metra, M; Perlini, S; Oltrona-Visconti, L
Abstract: Background: Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic, literature data are progressively accumulating, attesting to the possible prognostic role of cardiac troponins in patients who need hospitalization because of COVID-19 infection. Purpose: To assess whether myocardial injury (measured by high sensitivity troponins) is an independent cause of disease severity and prognosis. Methods: We performed a patient-level metanalysis (PROSPERO ID: CRD42020213209) in unselected patients hospitalized because of COVID-19 infection in whom the severity of respiratory failure was also evaluated at admission. To allow for comparison, troponin values were normalized to their threshold levels to obtain a normalized troponin (nTn) value which was used as a continuous variable in all analysis. Results: A total of 722 patients were included in the analysis. Of note, patients who had elevated troponins at hospital admission had a significantly lower oxygenation status than those with normal nTn (PaO2/FiO2 232±215 vs. 276±124 mmHg/%; p<0.001). On the contrary, those with cardiovascular comorbidities had similar PaO2/FiO2 but higher nTn than those without (5.6817 vs. 2.1110 ng/mL; p=0.002). After a median follow-up of 14 days, 180 deaths were observed. At multivariable regression analysis, age, male sex, moderate-severe renal dysfunction (eGFR <30 mL/min/m 2 ) and lower PaO2/FiO2, were independent predictor of death (igure 1). The restricted cubic spline curves in Figure 2A and 2B show the hazard ratios (HRs) and 95% confidence interval for death according to nTn and PaO2/FiO2 levels as continuous variables. A linear increase in the HR is observed with lower PaO2/FiO2 values below the normal value of 300. On the contrary, the nTn spline curve is near-flat with large confidence interval for values above the normality thresholds. Conclusion: In patients hospitalized for COVID-19, mortality is mainly driven by gender, age and respiratory failure while myocardial damage is not an independent predictor of worse survival when respiratory function is accounted for. Funding Acknowledgement: Type of funding sources: None.